Development and psychometric properties of teamwork scale in resuscitation: A sequential exploratory mixed-method study - Mohammad Hosseini; Abbas Heydari; Hamidreza Reihani; Hossein Kareshki (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Non-technical skills as a complement to technical skills have become increasingly important in cardio-pulmonary resuscitation, and teamwork is one of the most prominent of these skills. Because of the limited number of tools introduced and validated for measuring teamwork in resuscitation, this study was conducted to develop and evaluate the psychometric properties of the Teamwork Scale in Resuscitation (TSR). MATERIALS AND METHODS: This study was a sequential exploratory mixed-method study and was conducted between March 2020 and April 2021 and in two phases. In the first phase (qualitative), semi-structured interviews were performed with resuscitation team members who were selected using a purposeful sampling method with maximum variation in terms of experience, level of education, age, and gender. Using directed qualitative content analysis, the data were analyzed and the primary item pool was developed. In the second phase (quantitative), assessing face, content, and construct validity as well as reliability via the internal consistency and stability, the psychometric properties of the instrument are evaluated. RESULTS: The initial tool consisted of 54 items; after assessing the face validity, ten items were removed during content validity, and the final tool consisted of 44 items and three main categories including the essential prerequisites for resuscitation, leadership, and teamwork, which was scored based on a 5-point Likert scale from strongly disagree to strongly agree. The convergent validity and concurrent validity of the tool were confirmed. The reliability of the instrument was also confirmed using Cronbach's alpha test and re-test and the intra-class correlation coefficient (ICC) between raters. CONCLUSION: The validity and reliability of TSR for measuring teamwork in resuscitation in a simulated environment are approved. Further studies are suggested for different contexts of resuscitation and with trained raters to evaluate its use in real resuscitation situations.